Student Worksheets Integrated Augmented Reality Based on Physics Learning Project Models to Improve Students' Scientific Creativity in High School - Sumo, Maimon; Budiyanto, Ratno; Mulyadi, Syifaul Aini (Navigation Physics : Journal of Physics Education, 2025)
Scientific creativity is an important skill in 21st century learning. In practice, many students still have difficulty in developing ideas, exploring, and solving problems innovatively. Various previous studies have developed teaching materials based on Project Based Learning (PjBL) and Augmented Reality (AR) separately. However, none have integrated the two to improve scientific creativity. Based on the results of previous research studies, this study aims to develop student worksheets (LKPD) based on PjBL integrated with AR to improve the scientific creativity of high school students. The research method used is Research & Development (R&D) from ADDIE which consists of five stages, namely analysis, design, development, implementation, and evaluation. Based on the results of previous research studies, both in terms of methods, approaches and use of physics learning media, there is a research gap, the gap between this research and previous research is the integration between AR technology and project-based LKPD. The integration of AR with project-based LKPD simultaneously is something new in this study. This integration will provide a new experience that is more interactive and interesting in the physics learning process. The results of the study showed that the results of the validity test by three experts obtained an average validity score of 3.91 (98%) with a very valid category and a reliability score reaching 95.6% with a reliable category. Thus, this student worksheet is declared valid, practical, and effective in improving the scientific creativity of high school students. The limitation of this study is that this study has only reached the validation stage so that it needs to be implemented in more high schools.